2010
DOI: 10.1038/ismej.2010.192
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus supply drives rapid turnover of membrane phospholipids in the diatom Thalassiosira pseudonana

Abstract: In low-phosphorus (P) marine systems, phytoplankton replace membrane phospholipids with nonphosphorus lipids, but it is not known how rapidly this substitution occurs. Here, when cells of the model diatom Thalassiosira pseudonana were transferred from P-replete medium to P-free medium, the phospholipid content of the cells rapidly declined within 48 h from 45±0.9 to 21±4.5% of the total membrane lipids; the difference was made up by non-phosphorus lipids. Conversely, when P-limited T. pseudonana were resupplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(160 citation statements)
references
References 15 publications
9
148
2
1
Order By: Relevance
“…With less phospholipids in the membrane, the balance of IP-DAGs is expected to come from glycolipids and betaine lipids. The particular substitutions that have been observed in cultures are SQDG substituting for PG, and betaine lipids substituting for PC (Benning et al, 1993(Benning et al, , 1995Martin et al, 2011;Van Mooy et al, 2006, 2009. Across the Mediterranean, the ratios of SQDG:PG and betaine lipids:PC were both highest in the east.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…With less phospholipids in the membrane, the balance of IP-DAGs is expected to come from glycolipids and betaine lipids. The particular substitutions that have been observed in cultures are SQDG substituting for PG, and betaine lipids substituting for PC (Benning et al, 1993(Benning et al, , 1995Martin et al, 2011;Van Mooy et al, 2006, 2009. Across the Mediterranean, the ratios of SQDG:PG and betaine lipids:PC were both highest in the east.…”
Section: Discussionmentioning
confidence: 95%
“…The variation of IP-DAGs with different microbial groups has been well studied in cultures (Oliver and Colwell, 1973;Guschina and Harwood, 2006;Kato et al, 1996;Van Mooy et al, 2006), and some work has also been done measuring the diversity of IP-DAGs in microbial groups from environmental samples (Popendorf et al, 2011). The physiological response has also been well studied in monocultures (Benning et al, 1993(Benning et al, , 1995Martin et al, 2011;Van Mooy et al, 2009), however it remains to be shown whether the influence of changes in physiology can be detected in changes in IP-DAGs in a natural, mixed planktonic community.…”
Section: Factors Influencing Ip-dag Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Those peaks could potentially refer to diphosphatidylglycerol, phosphatic acid, the unidentified sulfur-containing lipids or DGCC (Kates and Volcani 1966;Opute 1974b;Martin et al 2011).…”
Section: Lipid Class Compositionmentioning
confidence: 99%
“…This modulation of P-containing biochemicals results in basin-scale relationships between P availability and biomass carbon-to-phosphorus (C:P) ratios (13). Presently, the only class of molecules known to consistently contribute to these gradients in cellular P are lipids because P stress in phytoplankton triggers substitution of non-P-membrane lipids for phospholipids, such as the sulfolipid sulfoquinovosyldiacylglycerol (SQDG) for the phospholipid phosphatidylglycerol (PG) (1,14). However, lipid substitution alone probably cannot account for the full range of C:P observed in the ocean, and yet an understanding of other biochemical drivers of the C:P gradient remains elusive.…”
mentioning
confidence: 99%